High-affinity monoclonal antibodies for aflatoxins and their application to solid-phase immunoassays. - Groopman, J D (1984)
Monoclonal antibodies specific for aflatoxin B1, aflatoxin B2, aflatoxin M1, and the major aflatoxin-DNA adducts were obtained following fusion of mouse SP-2 myeloma cells with spleen cells of mice immunized with aflatoxin B1 covalently bound to bovine gamma globulin. The aflatoxin-modified protein used to immunize mice was produced chemically by activating aflatoxin B1 to a 2,3-epoxide derivative, which then covalently bound to the protein. One of the monoclonal antibodies isolated (2B11) was found to be a high-affinity IgM antibody with an affinity constant for aflatoxin B1, aflatoxin B2, and aflatoxin M1 of about 1 X 10(9) liters per mol. In a competitive radioimmunoassay using [3H]aflatoxin B1, 3 pmol (1 ng) of aflatoxin B1, aflatoxin B2, or aflatoxin M1 caused 50% inhibition with this antibody. The antibody also had significant cross-reactivity for the major aflatoxin-DNA adducts: 2,3-dihydro-2-(N7-guanyl)-3-hydroxyaflatoxin B1 and 2,3-dihydro-2-(N5-formyl-2',5', 6'-triamino-4'oxo-N5-pyrimidyl)-3-hydroxyaflatoxin B1. The antibody was also covalently bound to Sepharose-4B and used in a column-based solid-phase immunosorbent assay system. Aflatoxins added in vitro to phosphate buffer, human urine, human serum, or human milk at levels expected to be obtained in human samples acquired from environmentally exposed individuals were quantitatively recovered by applying the mixture to this antibody affinity column purification system. Preliminary studies using urine samples from rats injected with radiolabeled aflatoxin B1 have also indicated that aflatoxin metabolites can be isolated by these methods. Furthermore, we have found that the monoclonal antibody affinity columns can be regenerated for multiple use. Therefore, the monoclonal antibodies and their application to affinity chromatography represents a useful and rapid technique to purify environmentally occurring levels of this carcinogen and some of its metabolites for quantitative measurements.